(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In Lord ofthe Flies, British schoolboys are stranded on a tropical island. In anattempt to recreate the culture they left behind, they elect Ralph tolead, with the intellectual Piggy ascounselor. But Jack wantsto lead, too, and one-by-one, he lures the boys from civility and reason to thesavage survivalism of primeval hunters. In Lord of the Flies, WilliamGolding gives us a glimpse of the savagery that underlies even the mostcivilized human beings.